Organocatalytic synthesis of α,α–diaryl substituted α–amino acid derivatives by an interrupted three-component Ugi reaction - Glavač, Danijel; Jerić, Ivanka; Gredičak, Matija (2019)
An organocatalytic interrupted three-component Ugi reaction for the synthesis of α,α–diaryl α–amino acid derivatives is described. The transformation proceeds with a range of isocyanides and 3-aryl isoindolinone alcohols using Brønsted acid catalysts to afford products in good to excellent yields. Based on the obtained results, a reaction mechanism is proposed and discussed.
Bibliografija: 20 jed.
Summary.
Keywords: Organokatalitička sinteza -- Heterociklički spojevi -- Aminokiseline -- Indol -- Derivati -- Ugi reakcija -- Biološka aktivnost -- Antihipertenzivi -- Antikonvulzivno djelovanje -- Anksiolitici